1984
DOI: 10.2307/3576240
|View full text |Cite
|
Sign up to set email alerts
|

Dose- and Time-Related Quantitative and Qualitative Alterations in the Granulocyte/Macrophage Progenitor Cell (GM-CFC) Compartment of Dogs after Total-Body Irradiation

Abstract: The effects of single-dose total-body X irradiation (TBI) on the granulocyte/macrophage progenitor cell (GM-CFC) population in bone marrow and blood of dogs were studied for dose levels of 0.78 and 1.57 Gy up to 164 days after irradiation. The blood GM-CFC concentration per milliliter was depressed in the first 7 days in a dose-dependent fashion to 5-16% of normal after 0.78 Gy and to between 0.7 and 5% after 1.57 Gy. The bone marrow GM-CFC concentration per 10(5) mononuclear cells, on the other hand, was init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Thereafter the pool size decreased again to extremely low GM-CFC numbers. Several other studies in dogs have shown [17][18][19][20] that any damage by radiation to certain fractions of bone marrow will cause a depression in the concentration of GM-CFC in the blood for several weeks and months after the acute exposure. The results obtained from determinations of GM-CFC in the blood of the continuously irradiated dogs are presented in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…Thereafter the pool size decreased again to extremely low GM-CFC numbers. Several other studies in dogs have shown [17][18][19][20] that any damage by radiation to certain fractions of bone marrow will cause a depression in the concentration of GM-CFC in the blood for several weeks and months after the acute exposure. The results obtained from determinations of GM-CFC in the blood of the continuously irradiated dogs are presented in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…The whole-body irradiation at different stages of prenatal development affected also populations of haemopoietic cells located in different organs and having different recovery abilities (Koshimoto et al, 1994;Morris et al, 1991;Weinberg, 1983). This should result in different long-term functional impairments of the system both in developing and adult individuals (Gidali et al, 1985;Grande and Bueren, 1995;Nothdurft et al, 1984;Weinberg, 1983;Weinberg et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, exposure to gamma radiation at different stages of prenatal development affected different populations of haemopoietic cells located in different organs (Koshimoto et al, 1994;Morris et al, 1991). It interrupted ontogenesis of the mononuclear phagocyte system which is an exogenous source of microglia/macrophages acting in the nervous tissue following injury (Gidali et al, 1985;Grande and Bueren, 1995;Nothdurft et al, 1984;Weinberg, 1983;Weinberg et al, 1983). The recruitment of macrophages to the lesion site and their proliferation might, therefore, be modified in a way dependent on the stage of prenatal development at which the irradiation was performed.…”
Section: Introductionmentioning
confidence: 99%
“…PIDS was collected and pooled from three dogs at day 9 after total body irradition with 3 . 9 Gy (Nothdurft et al 1984) . For each experimental point three Petri dishes (Greiner, 35 mm) were prepared and incubated for 9 days at 37°C in a humidified atmosphere containing 5 per cent CO 2 .…”
Section: Bfu-e Culture In Vitromentioning
confidence: 98%